2008
DOI: 10.1007/s10565-008-9086-6
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa therapy reduces DNA damage in peripheral blood cells of patients with Parkinson’s disease

Abstract: Oxidative stress seems to play a major role in the pathogenesis of neurodegeneration. In Parkinson's disease (PD) patients, the dopaminergic neurons are subjected to oxidative stress resulting from reduced levels of antioxidant defenses such as glutathione and high amount of intracellular iron. Levodopa (LD) is widely used for the symptomatic treatment of PD, but its role in oxidative damage control is still unclear. The aim of this study was to analyze the presence of DNA damage in peripheral blood lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
(49 reference statements)
1
22
0
1
Order By: Relevance
“…Lymphocytes from PD patients display an increased incidence of micronuclei, single strand DNA breaks, and oxidized purine bases [109]. Interestingly, levodopa treatment seems to reduce this DNA damage in peripheral blood lymphocytes [110]. Markers of apoptosis, caspase-3, and Cu/Zn superoxide dismutase activity are increased in lymphocytes from people with PD [111].…”
Section: Adaptive Immunity (I): T Lymphocytes In Pdmentioning
confidence: 99%
“…Lymphocytes from PD patients display an increased incidence of micronuclei, single strand DNA breaks, and oxidized purine bases [109]. Interestingly, levodopa treatment seems to reduce this DNA damage in peripheral blood lymphocytes [110]. Markers of apoptosis, caspase-3, and Cu/Zn superoxide dismutase activity are increased in lymphocytes from people with PD [111].…”
Section: Adaptive Immunity (I): T Lymphocytes In Pdmentioning
confidence: 99%
“…Apart from baseline damage present in PD patients, L-Dopa does not seem to have an adverse effect, but rather a protective effect both on lymphocytes [72] and on human dopaminergic cell line [76].…”
Section: Discussionmentioning
confidence: 81%
“…These results were still left open the debate on L-Dopa until 2009, when our research group [72] analyzed the presence of DNA damage in peripheral blood lymphocytes [6] isolated from blood samples of nine PD patients and nine matched controls, during a controlled dosage and washout of L-Dopa. We evaluated the oxidative DNA damage fluctuation after L-Dopa intake through the standard and the Fpg-modified version of Comet assay.…”
Section: Oxidative Stress and Dna Damage: Evidences To Support The Prmentioning
confidence: 99%
“…Some studies (e.g. [68]) suggest a toxic effect of L-dopa on neuronal cell in vitro, while in vivo studies in animal models are contradictory. Since less than 5% of an oral dose of L-dopa is delivered to the brain, the remaining plasma levels of the drug undergo peripheral oxidative metabolism and may generate ROS.…”
Section: Influence Of L-dopa Treatment On the Level Of Oxidative Damamentioning
confidence: 99%
“…Since less than 5% of an oral dose of L-dopa is delivered to the brain, the remaining plasma levels of the drug undergo peripheral oxidative metabolism and may generate ROS. It is likely that the peripheral oxidation status in PD might be affected by L-dopa therapy [68]. The study of Spencer et al [69] showed that the augmented oxidative stress in PD patients treated with L-dopa might influence the degree of reduction of antioxidants (GSH), disturbed mitochondrial transport, and excessive oxidation of dopamine.…”
Section: Influence Of L-dopa Treatment On the Level Of Oxidative Damamentioning
confidence: 99%